EFEK PAPARAN BAHAN PEWARNA AZO TERHADAP PERUBAHAN INTI SEL KARIOLISIS EPITEL MUKOSA BUKAL PENGRAJIN BATIK DI YOGYAKARTA - , MUFIDANA AZIS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Azo dyes, which are often used in textille industrial of batik dyes stuff, were detected have potential cytotoxic effects in human body. These substances get into the body through respiratory tract that connected to oral cavity by pharynx. Cytotoxic substances could cause cell death (necrosis). Cell death characterized by nuclear changes of cell. One of those changes is karyolysis. Karyolysis is final stage of cell death that could be evaluated by exfoliative cytology method in buccal mucosa epithelial cell of oral cavity. This research is aimed to know the exposure effect of azo dyes in the increase of karyolysis nucleus in buccal mucosal epithelial cells of batik workers in Yogyakarta. Research made within cross sectional study. Subjects were 20 males divided into 2 groups, that is 10 treatment subjects and 10 controls. Treatment subjects criteria were batik dyeing workers who were exposed to azo dyes, while controls were healthy non batik workers who were not exposed to azo dyes. Buccal mucosa epithelial cell of oral cavity were taken using cytobrush and stained using modified Feulgen-Rossenbeck method. Then, indentify and calculate the cumulative frequency rate of karyolysis buccal mucosa epithelial cell per 1000 cells under light microscope. The data was analyzed by Independent Sample T-Test (p<0,05). This research result showed there were significant differences karyolysis number of buccal mucosa epithelial cell of oral cavity between batik workers group who were exposed to azo dyes and controls. As conclusion, the exposure of azo dyes affect the number of increasing karyolysis in buccal mucosa epithelial cell of batik workers oral cavity in Yogyakarta. The advancement value of karyolysis number in buccal mucosa ephitelial cell occured to increase as the advancing value of exposure duration to batik workers.